Asparagus Polysaccharide inhibits the Hypoxia-induced migration, invasion and angiogenesis of Hepatocellular Carcinoma Cells partly through regulating HIF1α/VEGF expression via MAPK and PI3K signaling pathway - Cheng, Wei (J Cancer, 2021)
Aim: Although there are so many treatment strategies used for hepatocellular carcinoma (HCC), the overall survival (OS) of HCC patients still remains very low. In our previous studies, asparagus polysaccharide (ASP) has been demonstrated to suppress proliferation, migration, invasion and angiogenesis of HCC cells under normoxic conditions in vitro. However, the inhibitory effects of ASP on the hypoxia-induced migration, invasion and angiogenesis of HCC cells still remain largely unexplored. Materials and methods: Cell Counting Kit-8 (CCK-8) assay, transwell assay, and tube formation assay were used to determine the effects of ASP on hypoxia-induced proliferation, migration, invasion and angiogenesis of HCC cells. ELISA, Western blotting analysis and immunofluorescence assay were used to confirm the effects of ASP on the expressions of HIF-1α and VEGF at the protein level. Moreover, effects of ASP on signaling pathway-related proteins were investigated by Western blotting analysis. Immunohistochemistry (IHC) assay was applied to test the effects of ASP on angiogenesis-associated proteins of tumor cells. Results: We showed that ASP effectively suppressed hypoxia-induced proliferation, migration, invasion and angiogenesis of SK-Hep1 and Hep-3B cells in a dose-dependent manner. In addition, the inhibitory effect of ASP might be partly attributed to down-regulation of HIF1α and VEGF proteins in SK-Hep1 and Hep-3B cells under hypoxic conditions. Moreover, signaling pathway study indicated that ASP significantly down-regulated the hypoxia-induced expressions of p-AKT, p-mTOR and p-ERK, while it had little effects on AKT, mTOR and ERK. Besides, SK-Hep1 xenograft tumor models in nude mice further confirmed that the inhibitory effect of ASP on xenograft tumors might be exerted partly via down-regulation of HIF1α and VEGF through blocking MAPK and PI3K signaling pathways. Conclusions: Our findings suggested that ASP suppressed the hypoxia-induced migration, invasion and angiogenesis of HCC cells partly through regulating HIF-1α/VEGF expression via MAPK and PI3K signaling pathways.